Dari Tanah, Hidup Bertumbuh: Jejak Rahmat Allah di Setiap Butir Debu - Hana Rofifah; Arkan Maulana Utama; Ali Akbar (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This article explores the manifestation of Allah's SWT mercy through the process of creation and the growth of life from the earth's most fundamental element: soil. Utilizing a multidisciplinary approach that encompasses ecological, theological, and philosophical perspectives, this research examines how every speck of dust and soil particle serves as a sacred medium that allows life to grow and flourish. A deep analysis is conducted on relevant Qur'anic verses and hadiths concerning the origins of humans and plants from the earth, highlighting the close connection between physical and spiritual existence. The article argues that biological processes and the natural cycles of growth from the soil are not mere coincidental phenomena, but rather tangible evidence of continuous divine love and providence. Key findings indicate that the recognition of "the trace of Allah's mercy" in every aspect of nature can foster a deeper ecological and spiritual awareness, encouraging humanity to cherish the earth as a sacred trust and an invaluable source of life.